2020
DOI: 10.1111/luts.12341
|View full text |Cite
|
Sign up to set email alerts
|

A double‐blind, randomized, placebo‐controlled, parallel study to evaluate the efficacy and safety of imidafenacin in patients with overactive bladder in Taiwan

Abstract: Objective: This study evaluated the efficacy and safety of imidafenacin 0.1 mg twice daily vs placebo for Taiwanese patients with overactive bladder (OAB) after a 12-week oral administration. Methods: This randomized, double-blind, placebo-controlled, two-arm, parallelgroup, prospective study enrolled 118 patients across 11 study sites in Taiwan. Subjects were randomized to imidafenacin or placebo in a 2:1 ratio and entered the 12-week treatment period. At the subsequent visits, efficacy outcome measures and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Finally, 33 trials with 35,939 patients (29 trials with 27,135 patients for anticholinergics vs placebo, and 9 trials with 8,804 patients for beta 3–adrenoceptor agonists vs placebo) were eligible for the analysis (Table 2). 10-42 Follow-up duration was 1-3 months. Mean patient age was 43.7-75.1 years, and the proportion of male study participants was 0%-100% (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Finally, 33 trials with 35,939 patients (29 trials with 27,135 patients for anticholinergics vs placebo, and 9 trials with 8,804 patients for beta 3–adrenoceptor agonists vs placebo) were eligible for the analysis (Table 2). 10-42 Follow-up duration was 1-3 months. Mean patient age was 43.7-75.1 years, and the proportion of male study participants was 0%-100% (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Twenty-nine RCTs ( 15 19 , 22 30 , 37 51 ) reported urgency episodes/d, including three 4-arm studies, eight 3-arm studies and 18 two-arm studies, containing a total of 14 treatment measures and a total sample size of 17,859 cases ( Figure-2 ). The results showed that FES8mg-QD was the most effective in reducing mean daily urgency incontinence episodes, followed by SOL10mg-QD, with no statistically significant difference between the two, but both showed significant improvements in efficacy compared to most other interventions.…”
Section: Resultsmentioning
confidence: 99%
“…Twenty-seven RCTs ( 14 19 , 22 , 24 26 , 29 31 , 35 38 , 40 44 , 46 48 , 53 , 54 ) reported voided volume per micturition, including three 4-arm studies, ten 3-arm studies, and fourteen two-arm studies containing 11 treatment measures with a total sample size of 9,426 cases ( Figure-2 ). Initially, subgroup regression analysis was performed due to inconsistencies.…”
Section: Resultsmentioning
confidence: 99%